Case report: Fully endoscopic microvascular decompression for glossopharyngeal neuralgia - Jiang, Haotian; Zhou, Dewei; Wang, Pan; Zeng, Longwei; Liu, Jie; Tang, Chao; Zhang, Gang; Tan, Xiaorong; Wu, Nan (Frontiers in Surgery, 2023)
With the development of endoscopic technology, endoscopy has been widely used in many neurosurgery operations, such as microvascular decompression. And, microvascular decompression is an effective method to treat glossopharyngeal neuralgia, trigeminal neuralgia, facial spasm, etc. The purpose of this study is to investigate the efficacy of fully endoscopic microvascular decompression in the treatment of glossopharyngeal neuralgia. We reviewed a patient with glossopharyngeal neuralgia in our department, whose main clinical manifestation was recurrent left ear and facial pain for 3 years. Then he underwent fully endoscopic microvascular decompression. After the operation, the pain in the left ear and face was significantly relieved, and there was no recurrence after 6 months of follow-up. In this study, we describe a case of glossopharyngeal neuralgia successfully treated by full endoscopic microvascular decompression, which shows that endoscopy has certain advantages in microvascular decompression, and fully endoscopic microvascular decompression is an effective method for glossopharyngeal neuralgia.